Five newly recorded species of bat (Mammalia, Chiroptera) from the UNESCO World Heritage Niah National Park, Sarawak, Malaysia, with an updated checklist of bats in the park - Faisal Ali, Anwarali Khan; Muhd Amsyari, Morni; Muhammad Amin Iman, Azmi; Nur Iylia Maisarah, Baharom; Muhammad Danish Haqeem, Mohd Khairi; Asfa Hanis, Mohamad Azmi; Victor Lee, Sien; Julius William, Dee; Emy Ritta, Jinggong; Nor Al-Shuhadah, Sabarudin; Nur Afiqah Aqilah, Azhar; Sultana Parvin, Habeebur Rahman (Pensoft Publishers, 2025)
Five species of bat—Myotis gomantongensis Francis & Hill, 1998, Murina suilla (Temminck, 1840), Kerivoula intermedia Hill & Francis, 1984, Phoniscus jagorii (Peters, 1866), and Miniopterus magnater Sanborn, 1931—are newly recorded from Niah National Park, Sarawak, Malaysia. We also present an updated checklist of bat species compiled from seven sampling efforts conducted between 1958 and 2025. A total of 43 bat species from nine families have been recorded to date in the park. This species list serves as a baseline for bat conservation in this UNESCO World Heritage Site.